2018
DOI: 10.1021/acsearthspacechem.8b00168
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glyoxal on the Catalytic Oxidation of S(IV) in Acidic Aqueous Media

Abstract: The role of glyoxal in S­(IV) oxidation in acidic aqueous solutions catalyzed by iron in the form of aqueous Fe3+ ions and solid iron oxide was investigated under different experimental conditions. It is found that the rate of Fe3+(aqueous (aq)) ion-catalyzed S­(IV) oxidation decreases in the presence of glyoxal. The results of mass spectral analysis and infrared spectra suggest that the trapping of SO4 – radicals, as well as the formation of glyoxal–S­(IV) adducts, are responsible for this inhibition effect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…First, at receptor sites similar to the one in this work, failure to consider this Fe-mediated oxalate photodegradation loss pathway has the potential to significantly overestimate the aqueous secondary organic aerosol production . Second, the influence of the oxalate–Fe complex on sulfur oxidation is likely different during nighttime when the oxalate–Fe complex may suppress the oxidation of sulfur, ,, than in the daytime when the Fe redox reaction facilitated by oxalate would produce a considerable amount of O 2 • , HO 2 , and H 2 O 2 , which is known to be an effective oxidant of S­(IV) . A recent field study found an enhanced role of transition metal ion catalysis on coarse mineral dust during in-cloud SO 2 oxidation, and emphasized its importance as a dominant in-cloud oxidation pathway .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…First, at receptor sites similar to the one in this work, failure to consider this Fe-mediated oxalate photodegradation loss pathway has the potential to significantly overestimate the aqueous secondary organic aerosol production . Second, the influence of the oxalate–Fe complex on sulfur oxidation is likely different during nighttime when the oxalate–Fe complex may suppress the oxidation of sulfur, ,, than in the daytime when the Fe redox reaction facilitated by oxalate would produce a considerable amount of O 2 • , HO 2 , and H 2 O 2 , which is known to be an effective oxidant of S­(IV) . A recent field study found an enhanced role of transition metal ion catalysis on coarse mineral dust during in-cloud SO 2 oxidation, and emphasized its importance as a dominant in-cloud oxidation pathway .…”
Section: Resultsmentioning
confidence: 92%
“…First, at receptor sites similar to the one in this work, failure to consider this Fe-mediated oxalate photodegradation loss pathway has the potential to significantly overestimate the aqueous secondary organic aerosol production. 12 Second, the influence of the oxalate−Fe complex on sulfur oxidation is likely different during nighttime when the oxalate−Fe complex may suppress the oxidation of sulfur, 55,104,105 than in the daytime when the Fe redox reaction facilitated by oxalate would produce a considerable amount of O 2…”
Section: H C O (G) H C O (Aq) Hc O (Aq) Hmentioning
confidence: 99%
“…Analogous to OH radical chemistry, oxalate production is possible from the glyoxal oxidation by Cl • . Note that glyoxal does not directly bind with Fe 3+ and hence the decay of glyoxal (Figure S17) is most likely due to its reaction with chlorine radicals. When the estimated Cl • concentration of 10 –14 M (Figure S12) is taken, the reaction rate constant of Cl • and glyoxal is calculated to be 2.4 × 10 8 M –1 s –1 (Text S6), which falls in the reported reaction rate constants of Cl • and other carbonyl compounds. , The photochemistry of aqueous particles containing both organic and inorganic compounds warrants additional investigations.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…38−40 All of these reactions require the formation of inorganic S(VI) species prior to reaction with reactive organic intermediates. Organosulfur species have been found to form directly from SO 2 and CC/ CO double bonds, 40−43 which can be further catalyzed by TMI, 44,45 highlighting the potential for SO 2 to directly form OS in the atmosphere.…”
Section: ■ Introductionmentioning
confidence: 99%